Prediction of production rate for cultivable land correlating soil quality parameters and weather condition - Hassan, Mehedi; Rahman, S.M. Mushfiqur; Sobhani, Shadman (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2023.